Crime does not pay ; The CP Lopez story ; The Sariwang musika ni Joey Ayala [videorecording] - Lazaro, Cheche; Valdes, Luchi Cruz. (Quezon City Probe Productions, 1991)
Crime does not pay deals with the interview of arrested kidnappers. The second part is about the kidnapping and killing of CP Lopez, a DLSU student from Bacolod. Sariwang Musika is about Joey Ayala and his music.
Crime does not pay (14 min.) -- The CP Lopez story (14 min.) -- The Sariwang musika ni Joey Ayala (19 min.)
VHS.
Host, Luchi Cruz-Valdes ; Reporter, David Celdran
Keywords: Ayala, Joey; Lopez, Christopher Pio Valderama; Kidnapping -- Philippines